PcsB Expression Diversity Influences on Streptococcus mitis Phenotypes Associated With Host Persistence and Virulence - Harth-Chu, Erika N.; Alves, Lívia A.; Theobaldo, Jéssica D.; Salomão, Mariana F.; Höfling, José F.; King, William F.; Smith, Daniel J.; Mattos-Graner, Renata O. (Frontiers in Microbiology, 2019)
S. mitis is an abundant member of the commensal microbiota of the oral cavity and pharynx, which has the potential to promote systemic infections. By analyzing a collection of S. mitis strains isolated from the oral cavity at commensal states or from systemic infections (blood strains), we established that S. mitis ubiquitously express the surface immunodominant protein, PcsB (also called GbpB), required for binding to sucrose-derived exopolysaccharides (EPS). Immuno dot blot assays with anti-PcsB antibodies and RT-qPCR transcription analyses revealed strain-specific profiles of PcsB production associated with diversity in pcsB transcriptional activities. Additionally, blood strains showed significantly higher levels of PcsB expression compared to commensal isolates. Because Streptococcus mutans co-colonizes S. mitis dental biofilms, and secretes glucosyltransferases (GtfB/C/D) for the synthesis of highly insoluble EPS from sucrose, profiles of S. mitis binding to EPS, biofilm formation and evasion of the complement system were assessed in sucrose-containing BHI medium supplemented or not with filter-sterilized S. mutans culture supernatants. These analyses showed significant S. mitis binding to EPS and biofilm formation in the presence of S. mutans supernatants supplemented with sucrose, compared to BHI or BHI-sucrose medium. In addition, these phenotypes were abolished if strains were grown in culture supernatants of a gtfBCD-defective S. mutans mutant. Importantly, GtfB/C/D-associated phenotypes were enhanced in high PcsB-expressing strains, compared to low PcsB producers. Increased PcsB expression was further correlated with increased resistance to deposition of C3b/iC3b of the complement system after exposure to human serum, when strains were previously grown in the presence of S. mutans supernatants. Finally, analyses of PcsB polymorphisms and bioinformatic prediction of epitopes with significant binding to MHC class II alleles revealed that blood isolates harbor PcsB polymorphisms in its functionally conserved CHAP-domain, suggesting antigenic variation. These findings reveal important roles of PcsB in S. mitis-host interactions under commensal and pathogenic states, highlighting the need for studies to elucidate mechanisms regulating PcsB expression in this species.